Lexikon of the Hispanic Baroque : Transatlantic Exchange and Transformation - Mills, Kenneth, 1964-; Levy, Evonne Anita, 1961- (Book collections on Project MUSE., 2013)
This book explores the cultural transfers and transformations that define the transatlantic Spanish world in the Baroque era.